Convergence and hybrid information technology 5th International Conference, ICHIT 2011, Daejeon, Korea, September 22-24, 2011. Proceedings - International Conference on Convergence Information Technology 2011 Taejon-si, Korea); Lee, Geuk.; Howard, Daniel; Ślęzak, Dominik; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
This book constitutes the refereed proceedings of the 5th International Conference on Convergence and Hybrid Information Technology, ICHIT 2011, held in Daejeon, Korea, in September 2011. The 94 revised full papers were carefully selected from 323 initial submissions. The papers are organized in topical sections on communications and networking, intelligent systems and applications, sensor network and cloud systems, information retrieval and scheduling, hardware and software engineering, security systems, robotics and RFID Systems, pattern recognition, image processing and clustering, data mining, as well as human computer interaction.
Electronic reproduction.
Keywords: Computer science -- Congresses; Computer networks -- Congresses; Information technology -- Congresses